German Assyriology: A Discipline in Troubled Waters - Renger, Johannes (The betrayal of the humanities, 2022)
One of Germany’s proudest contributions to the humanities is Assyriology, the study of the languages and civilizations of ancient Mesopotamia. Despite its small numbers as a discipline, Assyriology provides a crucial window into the beginnings of western civilization—a window that had been quite literally buried in the sand for more than two millennia until the recovery and decipherment of cuneiform literature in the nineteenth century. Germans, including German Jews, played a crucial role in the development and consolidation of this discipline. In “German Assyriology (1933–1945): A Discipline in Troubled Waters,” Johannes Renger details how Assyriology in Germany was severely affected after 1933 by the Nazi civil service laws and the widespread academic drive to read the Aryan myth back into the reconstruction of ancient history. On the one hand, the number of German Assyriologists was devastated by emigration due to Nazi policy against Jewish scholars and political opponents of the regime. On the other hand, the remaining scholars’ compliance with Nazi policy undermined the integrity of the discipline.